Net Community Production, Dissolved Organic Carbon Accumulation, and Vertical Export in the Western North Atlantic - Baetge, Nicholas; Graff, Jason R.; Behrenfeld, Michael J.; Carlson, Craig A. (Frontiers in Marine Science, 2020)
The annual North Atlantic phytoplankton bloom represents a hot spot of biological activity during which a significant fraction of net community production (NCP) can be partitioned into dissolved organic carbon (DOC). The fraction of seasonal NCP that is not respired by the heterotrophic bacterial community and accumulates as seasonal surplus DOC (∆DOC) in the surface layer represents DOC export to the upper mesopelagic zone, and in the North Atlantic this is facilitated by winter convective mixing that can extend to depths >400 m. However, estimates of ∆DOC and vertical DOC export for the western North Atlantic remain ill-constrained and the influence of phytoplankton community structure on the partitioning of seasonal NCP as ∆DOC is unresolved. Here, we couple hydrographic properties from autonomous in situ sensors (ARGO floats) with biogeochemical data from two meridional ship transects in the late spring (~ 44 – 56˚N along ~ -41˚W) and early autumn (~ 42 – 53˚N along ~ -41˚W) as part of the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES). We estimate that 4 – 35% of seasonal NCP is partitioned as ∆DOC and that annual vertical DOC export ranges between 0.34 – 1.15 mol C m-2 in the temperate and subpolar North Atlantic. Two lines of evidence reveal that non-siliceous picophytoplankton, like Prochlorococcus, are indicator species of the conditions that control the accumulation of DOC and the partitioning of NCP as ∆DOC.